THE PEMBERIAN SENAM AEROBIK INTENSITAS RINGAN LEBIH MENURUNKAN PERSENTASE LEMAK SUBKUTAN DIBANDINGKAN INTENSITAS SEDANG PADA MAHASISWI FISIOTERAPI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Wisnu Saputra, I Made; Nurmawan, Sutha; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia; Vol 3 No 2 (2015): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2015.v03.i02.p04)
Overweight is generally caused as an imbalance between energy intake and calorie burning through physical activity. To overcome the overweight, an effective exercise is needed, one of them is aerobic exercise. Aerobic dance could be classified into low, moderate, and high intensity. The purpose of this study are to determine whether low intensity aerobic dance can decrease the percentage of subcutaneous fat more than moderate intensity. Experimental research was done with pre and post test two group designs. Sample of 22 subjects were divided into low intensity aerobic dance group and moderate intensity aerobic dance group, each group consisting of 11 subjects. The percentage of subcutaneous fat was calculated by using formula of Jackson and Brozek. Data analysis using Independent T-Test the mean difference obtained in the low intensity aerobic dance on triceps, suprailliaca, and middle quadriceps region respectively 1,33±0,98, 1,76±1,41, 3,21±1,52. The mean difference obtained in the moderate intensity aerobic dance on triceps, suprailliaca, and middle quadriceps region respectively 1,08±1,04, 1,56±1,76, 1,65±1,52. The conclusion is low intensity aerobic dance group significantly decrease the percentage of subcutaneous fat 20,02% more than moderate intensity aerobic dance group 12,04% on middle quadriceps region.
Keywords: Aerobic dance, percentage of subcutaneous fat.